2006
DOI: 10.1117/1.2345189
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for patterned fabric inspection using Bollinger bands

Abstract: This paper introduces a new application of Bollinger bands for defect detection of patterned fabric. A literature review on previous designed methods for patterned fabric defect detection will be depicted. For data analysis, Bollinger bands are calculated based on standard deviation and are originally used in the financial market as an oversold or overbought indicator for stock. The Bollinger bands method is an efficient, fast and shift-invariant approach, that can segment out the defective regions on the patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 40 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…5 However, the second phase is newly added to evaluate the degree of success of the proposed method in detecting defects. Each image is of size 256 × 256 in 24-bit depth.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, the second phase is newly added to evaluate the degree of success of the proposed method in detecting defects. Each image is of size 256 × 256 in 24-bit depth.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…5, the final detection result is not greatly affected if the values of m and n are approximately equal to or greater than the lengths of the row and column of a repetitive unit. 5 Hence, it is observed that the original BB method can deal with most defect types, especially those with large defects such as dirty yarn [ Fig. 5 Fig.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10] Many algorithms such as mathematical morphology method, 2 auto-correlation function method, 3 and co-occurrence matrixes method 4 have been designed for fabric defect detection. [2][3][4][5][6][7][8][9][10] Many algorithms such as mathematical morphology method, 2 auto-correlation function method, 3 and co-occurrence matrixes method 4 have been designed for fabric defect detection.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been used in completely different contexts such as identifying fabric defects during manufacturing (Ngan and Pang, 2006), although an academic literature search reveals few documented uses outside of finance and none in health care.…”
Section: Bollinger Bandsmentioning
confidence: 99%